2012
DOI: 10.1002/jcu.21929
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of successful labor induction using transvaginal sonographic cervical measurements

Abstract: Transvaginal sonographic cervical measurements can predict the successful labor induction, especially when associated to clinical analysis (Bishop's score).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
(50 reference statements)
0
14
1
Order By: Relevance
“…With these components, the different studies produced new scores or algorithms, allowing one to divide patients into subgroups with different labor induction prognoses. [29][30][31][32][33][34][35][36] Although these models are more complex with several variables to be accounted for, their predictive values appear superior to any factor used alone.…”
Section: Predicting the Success Of Labor Inductionmentioning
confidence: 99%
“…With these components, the different studies produced new scores or algorithms, allowing one to divide patients into subgroups with different labor induction prognoses. [29][30][31][32][33][34][35][36] Although these models are more complex with several variables to be accounted for, their predictive values appear superior to any factor used alone.…”
Section: Predicting the Success Of Labor Inductionmentioning
confidence: 99%
“…Labor induction is one of the most common procedures in obstetrics, used in up to 20% of pregnancies …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, predicting the success of labor induction in the early stages is a key aspect in planning better labors in order to reduce maternal-fetal risks and healthcare costs. Obstetric parameters have been previously used to predict labor induction success, including maternal-fetal characteristics and cervical status such as maternal age, height, weight, birth weight, cervical length and Bishop score, among others [6][7][8], although not with a high degree of accuracy. Several studies have indicated that EHG could be useful in identifying the efficiency of uterine contractions due to the fact that term or preterm labor EHG-bursts differ from non-true labor bursts [19,20,28,38].…”
Section: Discussionmentioning
confidence: 99%
“…The most common method of predicting success is based on cervix assessment by the Bishop score [4], although this method is subjective with poor reproducibility [5]. Other obstetric variables have been used for this purpose, such as cervical length, maternal age, height, weight, parity, and birth weight [6][7][8][9][10]. Some of the predictive capacity values given in the literature are in the area under the curve (AUC) of the receiver operating characteristic (ROC) curves (0.689 for cervical length and 0.72 for cervical dilatation [8]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation